Faktor Penentu Produksi Tanaman Buah Naga Merah (Hylocereus polyrhizus) - Ledoh, Neta Ayu Puspita; Pellokila, Marthen Robinson; Lango, Alfetri N. P. (Undana Press, 2023)
This research was conducted in Kolobolon Village, Lobalain District, Rote Ndao District. The purpose of this study was to find out the general description of red meat dragon fruit (Hylocereus polyrhizus) cultivation techniques and to find out the factors that determine the production of red meat dragon fruit (Hylocereus polyrhizus). The variables used in this study were land area, organic fertilizers, pesticides, labor and number of plants. Using primary and secondary data. Data collection techniques with interviews and documentation methods. Data processing was carried out using the SPSS version 26 program using the Cobb-Douglas production function.The results showed that all stages of agricultural activity started from seeding, tillage, support poles, planting, fertilizing, pruning, watering, pest control, harvesting, and post-harvesting. Based on the analysis using the Cobb-Douglas production function, the following results are obtained: : Y = 7.683 X1–0,060 X20,304 X3– 0,011X40,355X50,208. The results of the simultaneous F test showed that the independent variable had an effect on the yield of red flesh dragon fruit (Hylocereus polyrhizus) of 24.261. Partial test (t) shows that organic fertilizer, labor and the number of plants significantly affect the yield of dragon fruit with red meat (Hylocereus polyrhizus). Meanwhile, area and pesticide variables had no significant effect on the yield of red meat dragon fruit (Hylocereus polyrhizus). The Adjusted R2 value is 0.847. showed that 84.70% of red meat dragon fruit (Hylocereus polyrhizus) production could be explained by area variables, organic fertilizers, pesticides, labor and number of plants. While the remaining 15.30%, this ratio is explained by other factors that are not included in the regression model.